French Norms for the Harvard Group Scale of Hypnotic Susceptibility, Form A. Issue 2 (3rd April 2017) - Anlló, Hernán; Becchio, Jean; Sackur, Jérôme
Abstract: The authors present French norms for the Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A). They administered an adapted translation of Shor and Orne's original text (1962) to a group of 126 paid volunteers. Participants also rated their own responses following our translation of Kihlstrom's Scale of Involuntariness (2006). Item pass rates, score distributions, and reliability were calculated and compared with several other reference samples. Analyses show that the present French norms are congruous with the reference samples. Interestingly, the passing rate for some items drops significantly if "entirely voluntary" responses (as identified by Kihlstrom's scale) are scored as "fail." Copies of the translated scales and response booklet are available online.